Sinergitas Program Studi dan Fakultas dalam Meningkatkan Jumlah Mahasiswa Baru: Studi pada Program Studi Hukum Ekonomi Syariah - Nurhotia Harahap; Nursaima Harahap (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Sharia Economic Law Study Program (HES) has a strategic role in equipping students with knowledge and skills that are relevant to the dynamics of sharia law and economics in the era of globalization. In the conditions of increasingly competitive university competition, synergy between study programs and faculties is an important strategy to increase the attractiveness of institutions and the number of new students. This study aims to analyze the role of institutional synergy between the HES Study Program and the Faculty of Sharia and Law UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan in an effort to increase new student admissions. This study uses a qualitative method with a case study approach. The data collection technique was carried out through in-depth interviews with faculty leaders, study program chairs, lecturers, and alumni; observation of campus promotion and introduction activities; as well as documentation studies on academic policies and student admission data. Data is analyzed descriptive-analytically through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that effective synergy between study programs and faculties, which is realized through the development of an adaptive curriculum, integrated promotion strategies, and collaboration with external parties such as legal practitioners and alumni, contributes significantly to improving the image of the institution and the number of new students. In addition, the involvement of all academic elements in promotional activities and campus introductions is able to create an inclusive academic environment and increase the interest of prospective students in the Sharia Economic Law Study Program.